High temperature inhibited the accumulation of anthocyanin by promoting ABA catabolism in sweet cherry fruits - Tan, Yue; Wen, Binbin; Xu, Li; Zong, Xiaojuan; Sun, Yugang; Wei, Guoqin; Wei, Hairong (Frontiers in Plant Science, 2023)
Color is an essential appearance characteristic of sweet cherry (Prunus avium L.) fruits and mainly determined by anthocyanin. Environmental factors play important roles in the regulation of anthocyanin accumulation. In this research, anthocyanin, sugar, plant hormone and transcriptome data were analyzed to reveal the effects of high temperature on fruit coloring and the related mechanism. The results showed that high temperature severely inhibited anthocyanin accumulation in fruit peel and slowed the coloring process. The total anthocyanin content in fruit peel increased by 455% and 84% after 4 days of normal temperature treatment (NT, 24 °C day/14 °C night) and high temperature treatment (HT, 34 °C day/24 °C night), respectively. Similarly, the contents of 8 anthocyanin monomers were significantly higher in NT than in HT. HT also affected the levels of sugars and plant hormones. The total soluble sugar content increased by 29.49% and 16.81% in NT and HT, respectively, after 4 days of treatment. The levels of ABA, IAA and GA20 also increased in both the two treatments but more slowly in HT. Conversely, the contents of cZ, cZR and JA decreased more rapidly in HT than in NT. The results of the correlation analysis showed that the ABA and GA20 contents were significantly correlated with the total anthocyanin contents. Further transcriptome analysis showed that HT inhibited the activation of structural genes in anthocyanin biosynthesis as well as the repression of CYP707A and AOG, which dominated the catabolism and inactivation of ABA. High temperature induces higher ABA catabolism and inactivation, leading to lower ABA levels and resulting in slow coloring. Taken together, these results suggest that ABA may be a key regulator in the high-temperature-inhibited fruit coloring of sweet cherry.